Association of youth impulsivity and use of e-cigarette devices, flavors, and frequency of use. (November 2022) - Davis, Danielle R.; Bold, Krysten W.; Morean, Meghan E.; Kong, Grace; Jackson, Asti; Simon, Patricia; Rajesh-Kumar, Lavanya; Krishnan-Sarin, Suchitra
Highlights: Higher behavioral impulsivity is related to youth vaping a greater number of flavors. Higher youth behavioral impulsivity is associated with more days of e-cigarette use. Self-control was not associated with days of e-cigarette use or products used. Using more e-cigarette device types was not associated with impulsivity in youth. Abstract: Introduction: Given high youth e-cigarette use, it is important to investigate how traits, like impulsivity, may be associated with youth e-cigarette use behaviors. The study aim is to determine if impulsivity is associated with trying more e-cigarette flavors and device types, and greater frequency of e-cigarette use. Method: Cross sectional survey data from CT high schoolers (n = 4875, 6 schools) were collected in 2019. Lifetime (ever) e-cigarette users (n = 2313) completed the Brief Barrett Impulsivity Scale, which contains two subscales; behavioral impulsivity and impaired self-control. Among lifetime users, associations between impulsivity subscales and number of e-cigarette flavors tried, e-cigarette devices tried, and past 30-day frequency of e-cigarette use were examined using regression models. Additionally, associations of impulsivity and use frequency were examined among only current e-cigarette users (≥1 day of use in past 30; n = 1327). School, age, race/ethnicity, vaping initiation age, other tobacco product use, and sex were included as covariates in models. Results: Higher behavioral impulsivity was associated with greater number of e-cigarette flavors tried (AOR: 1.06, 95% CI: 1.02, 1.11, p <.008) and higher frequency of past 30-day use both among ever and current e-cigarette users (AOR: 1.26, 95%CI:1.10, 1.44, p <.001; AOR: 1.12, 95%CI:1.02, 1.22, p <.02), but not number of e-cigarette devices tried. Impaired self-control was not associated with any outcomes. Conclusion: Youth with higher behavioral impulsivity may be more at risk for using more e-cigarette flavors and using e-cigarettes more frequently. Regulations aimed at reducing flavor availability among youth and interventions targeting impulsive behavior may be important for this population.